AN EVALUATION OF STUDENTS SKILLS AND EXPACTATIONS RELATED WITH THE JOB ASPIRATIONS - Muntean, Andreea Cipriana; Dobra, Iulian Bogdan (Annales Universitatis Apulensis Series Oeconomica, 2017)
The overall objective of the research is to evaluate the students' skills and aspirations, in order to highlight the professional features and opportunities they had acquired after graduation. Primary data were collected by questionnaire. The results can be used to describe the profile of the students from Economics with regard to the identification of skills that a company's employee or manager should have. The questionnaire tackled three aspects: a general theoretical one, the other focused on the transition from school to active life, and the last aimed at the students' skills and expectations. It was intended to outline a student profile by identifying the expectations and abilities of the persons surveyed, and also to identify the respondents' opinions on the attitude regarding the students' level of practical knowledge and on the importance of their theoretical professional training, their practical training and their professional experience for the future job.